2010
DOI: 10.1097/dad.0b013e3181cc8c7c
|View full text |Cite
|
Sign up to set email alerts
|

Nestin-Positive Stem Cells in Neurofibromas From Patients With Neurofibromatosis Type 1-Tumorigenic or Incidental?

Abstract: Although we found no difference in melanogenic cells in neurofibromas from patients with NF1 relative to the sporadic group, we did find a significant population of nestin-positive progenitor cells in neurofibromas from patients with NF1. In light of recent evidence linking formation of neural neoplasms such as neurofibroma to alterations in the self-renewal program of stem/progenitor cells, our findings reinforce the potentially tumorigenic role of nestin-positive progenitor cells in neurofibromas from patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Thus, it would be interesting to investigate Pax chromatin modifications in kidney tubules and Schwann cells during responses that involve dedifferentiation of injured cells and redifferentiation of their progeny. An understanding of this Pax epigenetic switching during homeostatic tissue repair may shed light on the aberrant processes of repair that may occur in chronic kidney disease and neurofibromatosis (Pongpudpunth et al, 2010). In addition, such an understanding could be applied to the therapeutic control of PAX gain of function in ARMS and other cancers.…”
Section: Aberrant Pax Gene Expression: Implications For Regeneration mentioning
confidence: 99%
“…Thus, it would be interesting to investigate Pax chromatin modifications in kidney tubules and Schwann cells during responses that involve dedifferentiation of injured cells and redifferentiation of their progeny. An understanding of this Pax epigenetic switching during homeostatic tissue repair may shed light on the aberrant processes of repair that may occur in chronic kidney disease and neurofibromatosis (Pongpudpunth et al, 2010). In addition, such an understanding could be applied to the therapeutic control of PAX gain of function in ARMS and other cancers.…”
Section: Aberrant Pax Gene Expression: Implications For Regeneration mentioning
confidence: 99%
“…Some nerve tumors of soft tissue are thought to be derived from stem cells. [9,10] These findings suggest that the present perineuroma were derived from neural stem cells.…”
Section: Discussionmentioning
confidence: 67%
“…In central neural tumors and some peripheral nerve tumors, in particular neurofibromatosis, are derived from neural stem cells. [9,10] However, there have been no cases of perineuroma, neurothekeoma, and nerve sheath myxoma with stem cell features.…”
Section: Introductionmentioning
confidence: 99%
“…Neurofibromas consist primarily of NMSCs [75][77] where malignant transformation is linked to NMSC hyperproliferation and detrimental effects on adjacent cells [78]. Importantly, in neurofibroma, it has been found that tumours have a significant population of stem cells [79] and although the origin of the stem cells remains unknown, Pongpudpunth et al [79] proposed that “formation of neurofibromas may be linked to alterations in the self-renewal program of peripheral nerve progenitor cells”.…”
Section: Discussionmentioning
confidence: 99%